Pencegahan Perilaku Bullying di Sekolah melalui Penggunaan Aplikasi Diary Online pada Siswa Madrasah Tsanawiyah Swasta (MTsS) Plus Tondano - Hamsah, Hamsah; Rorimpandey, Gladly Caren; HS, Fatimah; Hulu, Lena Enjelin; Mamonto, Nurmila (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Lack of understanding about bullying and the absence of media that can be used in preventing bullying are the main problems for community service partners. Through bullying prevention activities in schools using the Online Diary application, it is hoped that it can be a solution in preventing bullying behavior. The community service methods used are lecture, question and answer and practice methods. The community service stages consist of the preparation stage, implementation stage and evaluation stage. The results of the implementation of the activity provide solutions to partner problems. This can be seen from the increase in participant knowledge in understanding bullying and how to use the online diary application with an average percentage value increasing from the pre-test by 34.11% to 87.11% or from the sufficient category to the very good category. Overall, the activity was carried out and provided benefits to partners.